1998
DOI: 10.1021/ma971737k
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of l,l-Lactide Initiated by Aluminum Isopropoxide Trimer or Tetramer

Abstract: Kinetics of polymerization of l,l-lactide (LA) initiated with aluminum isopropoxide (Al(OiPr)3) trimer (A3) or tetramer (A4) was followed by polarimetry and by gel permeation chromatography (GPC). Results of the kinetic measurements show that A3 and A4 react with LA with different rates; namely, the k i(A 3 )/k i(A 4 ) ratios (where k i(A 3 ) and k i(A 4 ) denote the rate constants of initiation with A3 and A4, respectively) determined at 20, 50, 80 (THF solvent), and 120 °C (dioxane-1,4 solvent), are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
311
2
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(335 citation statements)
references
References 36 publications
16
311
2
6
Order By: Relevance
“…In GPC chromatograms monomodal molecular weight distribution was observed but the determination of true M n values from GPC analysis is doubtful because of the lack of appropriate standards (in some publications correction factors are used but such procedure may be questioned for relatively low molecular weight polymers) [18,19]. Therefore, for the determination of M n we relied mainly on 1 H NMR analysis which allowed the calculation of molecular weights more reliably by comparison of the intensities of signals corresponding to terminal methine group with those corresponding to methine groups from polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…In GPC chromatograms monomodal molecular weight distribution was observed but the determination of true M n values from GPC analysis is doubtful because of the lack of appropriate standards (in some publications correction factors are used but such procedure may be questioned for relatively low molecular weight polymers) [18,19]. Therefore, for the determination of M n we relied mainly on 1 H NMR analysis which allowed the calculation of molecular weights more reliably by comparison of the intensities of signals corresponding to terminal methine group with those corresponding to methine groups from polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Hiltunen et al [20] measured molar masses 2-3 times smaller by titration than by SEC. Kowalsky et al [21] and Save et al [23] reported the same feature and found that the error depends on the chemical structure of the polymer and its mass range. They proposed a correction factor ranging from 0.54 to 0.58 depending on the polymer.…”
Section: Comparison Of Molar Mass Data Obtained By 1 H-nmr and Secmentioning
confidence: 71%
“…The above comment illustrates one of the reasons why the determination of molar mass by SEC with a refractive index or light scattering detector for polyesters is controversial in chloroform. Several authors have recently highlighted that polystyrene-calibrated SEC measurements in chloroform overestimate the real M n -by at least 50% in the range above 10 4 g·mol -1 for poly("-caprolactone), polylactide and related copolyesters [18][19][20][21][22][23][24]. For these reasons, researchers have used complementary techniques such as MALDI-TOF mass spectrometry [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…Narrow molecular weight polystyrene standards were used to calibrate the instrument and a correction factor of 0.58 was applied to the M n according to the literature. 17 The MALDI-TOF mass spectrometry was performed with a Micromass MALDI micro MX mass spectrometer equipped with a UV (337 nm) laser. All mass spectra recorded in linear mode.…”
Section: Measurementsmentioning
confidence: 99%